STUDY OF THE EUROPEAN SOCIETY OF HYPERTENSION ON BLOOD PRESSURE CONTROL IN ESH EXCELLENCE CENTERS (BP CON ESH) - THE FIRST PRELIMINARY REPORT. (April 2021) - Jelakovic, Bojan; Triantafyllou, Areti; Doumas, Michael; Kalaitzidis, Rigas; Protogerou, Athanase; Kallistratos, Emmanouil; Stergiou, George; Moloberti, Alessandro; Giannattasio, Cristina; Marketou, Maria; Papadakis, Ioannis; Papadopoulos, Dimitrios; et al.
Abstract : Objective: To determine the BP control and identify associated global and local risk factors in ESH Excellence centers. Design and method: The first 4 consecutive adult patients coming to the visit in an Excellence center on a particular day who fulfill inclusion/exclusion criteria and singed informed consent were enrolled. Structured questionnaire was applied, BP and heart rate were measured using the same validated device with appropriate cuff. In centers with capability to perform unattended BP measurements (Omron HEM-907 XL) both methods were done in a random sequence. Body weight, height and waist circumference, laboratory data, ABPM and ECG done in past 3 months and BP values from medical records were entered into the eCRF. Figure. No caption available. Results: After the start in 12/2018 from overall 189 ESH Excellence centers, 80 centers (42.3%) from 24 different countries agreed to participate. Currently, 29 centers (36.3%) from 11 countries (45.8%) enrolled their patients. Patients' demographics and clinical characteristics are shown in Table 1, and average BP and heart rate values are presented in Table 2. Conclusions: This first interim analyses confirmed the feasibility of conducting BP CON ESH study among ESH Excellence centers. The preliminary data for attended BP measurements indicated mean BP values above the recommended targets in the 2018 ESC/ESH guidelines.